2021
DOI: 10.1002/adfm.202010743
|View full text |Cite
|
Sign up to set email alerts
|

Actuation of Three‐Dimensional‐Printed Nanocolloidal Hydrogel with Structural Anisotropy

Abstract: Polymer hydrogels exhibit actuation properties that result in reversible shape transformations and have promising applications in soft robotics, drug delivery systems, sensors, and microfluidic devices. Actuation occurs due to differential hydrogel swelling and is generally achieved by modulating hydrogel composition. Here a different approach to hydrogel actuation that originates solely from its structural anisotropy is reported. For 3D-printed single-layer hydrogels formed by cellulose nanocrystals (CNCs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 44 publications
0
63
0
Order By: Relevance
“…Over the past few decades, microfluidics (MFs) has emerged as a powerful platform for fundamental and applied research in cell biology, soft robotics, medicine, drug screening, materials science, and analytical chemistry ( Whitesides, 2006 ; Tian and Finehout, 2009 ; Young et al, 2012 ; Pak et al, 2015 ; Rajendra et al, 2015 ; Moore et al, 2017 ; Humayun et al, 2018 ; Khuu et al, 2019 ; Gevorkian et al, 2021 ). For all applications, the design of an MF device with optimized geometry is a vital first step of the engineering process, but the optimization process is usually conducted in a trial-and-error manner and is, therefore, time- and labour-intensive ( Chakraborty, 2010 ; Huang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, microfluidics (MFs) has emerged as a powerful platform for fundamental and applied research in cell biology, soft robotics, medicine, drug screening, materials science, and analytical chemistry ( Whitesides, 2006 ; Tian and Finehout, 2009 ; Young et al, 2012 ; Pak et al, 2015 ; Rajendra et al, 2015 ; Moore et al, 2017 ; Humayun et al, 2018 ; Khuu et al, 2019 ; Gevorkian et al, 2021 ). For all applications, the design of an MF device with optimized geometry is a vital first step of the engineering process, but the optimization process is usually conducted in a trial-and-error manner and is, therefore, time- and labour-intensive ( Chakraborty, 2010 ; Huang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have described the effects of oscillatory shear under a range of conditions in such systems [36][37][38][39][40][41][42], where continuous shear can crystalize colloidal monodisperse particles when there is a suitable fluid medium present. A notable variant of these methods is shear alignment in anisotropic ensembles [43,44]. As a fundamental distinction, POs do not contain a discrete fluid phase, and therefore cannot be directly compared to these systems of colloidal suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that many plants including pinecones exhibit actuating performance based on different local swelling behavior produced by the directional orientation of cellulose fibrils. [75,79] For instance, Gevorkian and coauthors showed a novel method to fabricate planar single-layer hydrogels with anisotropic structures. [75] The orientation of cellulose nanocrystals (CNCs) was achieved by lowering the temperature and subsequent photo-crosslinking with gelatin methacryloyl.…”
Section: Design and Fabrication Of Cellulose-based Actuators 21 Desig...mentioning
confidence: 99%